The Influence Of Work Culture And Work Discipline On Employee Performance At Advent Hospital Medan - Sarah, Hotmauli; Sjahri , Effendy; Patisina (Publisher Cv. Inara, 2023)
Hospital performance is very important to ensure that patients get the right care according to their needs. Hospital performance is also very important to ensure that hospitals can carry out their functions properly and efficiently, and are able to provide quality services to patients. This study aims to determine the effect of culture and work discipline on employee performance. This research was conducted at the Medan Adventist Hospital with a sample of 100 hospital employees. The results of the study show that the contribution of organizational citizenship behavior and social intelligence to performance is 72.0% so that a high work culture and discipline improve employee performance so that it motivates employees to work. Disciplined behavior will lead to productivity and end in performance.